TRANSFORMASI KOMUNIKASI KELUARGA DI ERA MEDIA SOSIAL ANTARA KEHANGATAN TATAP MUKA DAN TANTANGAN PRIVASI DIGITAL - Ahmad Alimuddin; Naharuddin SR (Universitas Islam Negeri Mataram, 2025)
The rapid development of social media has transformed family communication dynamics, presenting both opportunities for connectivity and challenges to privacy and emotional intimacy. This study explores the transformation of family interactions in the era of social media and the urgent need for a responsive family law framework in Indonesia. Using a qualitative approach with in-depth interviews, document analysis, and online observations, the research examines how platforms like WhatsApp and Instagram reshape family communication patterns and identifies emerging legal challenges, such as privacy violations and intergenerational conflicts. Findings reveal that while social media facilitates long-distance communication, 60% of respondents prefer face-to-face interactions for maintaining emotional closeness, highlighting the limitations of digital platforms in conveying emotional depth. Additionally, 20% reported privacy breaches, underscoring risks like unauthorized sharing of personal information. The study emphasizes the need for adaptive family law regulations, including amendments to child protection laws and digital mediation mechanisms, to address these challenges while preserving family values in Indonesia’s digital age.